Unpacking the Roles of Reading-to-Write and Writing-Only Approaches: A Comparative Case Study of Thai Undergraduate Students - Tatsanajamsuk, Pratabjai (rEFLections, 2024)
This comparative case study explores the roles of reading-to-write and writing-only approaches on students’ L2 writing skills. Six third-year English major students from a Thai university, with diverse proficiency levels, participated in the study. Data from students’ writing samples, semi-structured interviews, and observations were analyzed through quantitative and qualitative methods. The two approaches contributed differently to enhancing students’ English writing skills. The writing-only approach significantly improved grammatical accuracy, while the reading-to-write approach fostered the use of more complex grammar structures, particularly in argumentative writing. In terms of coherence and cohesion, both approaches proved equally productive. Language proficiency, learning styles, task demands, essay types, topic familiarity, and time limitations also impacted the utilization of each approach. These insights suggest a blended approach to teaching writing at the university level, integrating both reading and writing elements. However, the findings also underscore the importance of explicit instruction in grammar and reading to support students in developing robust writing skills.